Meningkatkan Kemampuan Menyanyikan Lagu Wajib Nasional dengan Metode Solfegio Di Sekolah Dasar - D Destrinelli; Mei Nur Wijayanti (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
This research aimed at improving the capability of singing the National Anthems of the students of class IV of SDN 111/I Muara Bulian by employing the Solfegio method. The results of the research are expected to be useful for the development of musical science (singing) in particular, to be a reference for the next research and to be an additional information as well as consideration for either teachers or schools to employ the Solfegio method during learning musics (singing).This class action research employed Kemis and Mc. Taggart model using phases such as : planning, action, observing, and reflecting. The subject of the research was thirty four students of class IV SDN 111/I Muara Bulian. The data were collected through observation and dual analysis, i.e. the descriptive qualitative analysis and the simple statistics quantitative analysis. Based on the results of the research, it can be concluded that to improve the capability of singing the National Anthems of the Students of Class IV SDN 111/I Muara Bulian can be accomplished through carrying out the Solfegio method during class musics (singing) by practicing to sing: (1) the musical scale, (2) the interval tone, and (3) the melody.